Signatures of Mesoscopic Transport in Single Non-Intentionally Doped GaN-Nanowire Field-Effect Transistors - Hergert, Hannes; Zscherp, Mario F.; Klement, Philip; Schörmann, Jörg; Chatterjee, Sangam; Klar, Peter J.; Elm, Matthias T.; Justus Liebig University Giessen (My University, 2024)
In this work, the fabrication and characterization of a fully functional field-effect transistor (FET) are addressed based on a non-intentionally doped GaN-nanowire FET (NW–FET). Universal conductance fluctuations (UCFs) are observed at temperatures below 140 K. In contrast to other reports in literature, UCFs appear in the analyzed NW–FET only under the influence of an electrical field when applying a gate voltage, while no UCF signatures are observed when performing magnetic-field-dependent measurements. The reason is the considerable impact of the applied voltage on the narrow conductive channel of the non-intentionally doped NW. The electrical field influences the Fermi level as well as the width of the depletion region, both changing the effective impurity distribution which determines the set of possible electron paths. The electric-field-induced variation of the set of electron paths correlates with a conductance variation, which leads to the occurrence of UCFs. Furthermore, the reliability of determining the phase coherence length lϕ from the NW–FET transfer characteristics is analyzed. It is shown that the value of lϕ is significantly affected by the choice of the gate voltage range due to the current dependence of the magnitude of the UCFs.
Keywords: ddc:530